EPSTI1 as an immune biomarker predicts the prognosis of patients with stage III colon cancer - Wang, Xitao; Cheng, Wei; Zeng, Xingzhi; Dou, Xiaolin; Zhou, Zhongyi; Pei, Qian (Frontiers in Immunology, 2022)
Objective: The poor prognosis and heterogeneity of stage III colon cancer (CC) suggest the need for more prognostic biomarkers. The tumor microenvironment (TME) plays a crucial role in tumor progression. We aimed to explore novel immune infiltration-associated molecules that serve as potential prognostic and therapeutic targets. Methods: TME immune scores were calculated using “TMEscore” algorithm. Differentially expressed genes between the high and low TME immune score groups were identified and further investigated through a protein-protein interaction network and the Molecular Complex Detection algorithm. Cox regression, meta-analysis and immunohistochemistry were applied to identify genes significantly correlated with relapse-free survival (RFS). We estimated immune infiltration using three different algorithms (TIMER 2.0, CIBERSORTx, and TIDE). Single-cell sequencing data were processed by Seurat software. Results: Poor RFS was observed in the low TME immune score groups (log-rank P < 0.05). EPSTI1 was demonstrated to be significantly correlated with RFS (P < 0.05) in stage III CC. Meta-analysis comprising 547 patients revealed that EPSTI1 was a protective factor (HR = 0.79, 95% CI, 0.65-0. 96; P < 0.05)). More immune infiltrates were observed in the high EPSTI1 group, especially M1 macrophage infiltration (P < 0.05). Conclusion: The TME immune score is positively associated with better survival outcomes. EPSTI1 could serve as a novel immune prognostic biomarker for stage III CC.